O przyczynach niektórych niepowodzeń dydaktycznych w stosowaniu koncepcji systemowego nauczania i uczenia się literatury w praktyce szkolnej = Some remarks on difficulties in applying the theory of systematic teaching learning in the school practice - Pasterniak, Wojciech (1935-2018) (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The most often appearing difficulties and errors in applying the theory of systematic teaching/learning in the school practice have been discurssed in the article.
Keywords: dydaktyka literatury